Numerical analysis of wave propagation and vibration of overhead transmission cable - Silva, Gabriel; Machado, Marcela; Dutkiewicz, Maciej; Santos, José Maria Campos dos (Revista Interdisciplinar de Pesquisa em Engenharia, 2020)
This paper presents a comparison of numerical methods used to model and analyse the vibration of overhead transmission line conductor. The cable vibration signature is expressed through the frequency response function (FRF) and the flexural wave propagation via dispersion diagram. The cable is modelled under the numerical background of the finite element, spectral element, spectral transfer matrix, and wave finite element methods. Efficacy, accuracy and computational effort to estimate the FRF and dispersion diagram results demonstrate the advantage and limitation of each technique. It is recommended to analyse the vibrations of the systems in different configurations of initial and boundary conditions because some initial condition likewise tensile force, changes the dynamic response and the type of waves. The numerical analysis investigates the natural frequency, mode shape and flexural waves estimated from the four methods for different tensile force and boundary condition.